Konsep Halalan Thayyiban dalam Al-Qur’an dan Relevansinya dengan Kesehatan Jiwa - Arsudin, Muhamad; Saad, Suadi; Kurni, Waesul; Masykur, Masykur (STAINI Press, 2024)
This article discusses the concept of halalan thoyyiba food in the Qur'an and its relevance to mental health. The concept includes an understanding of the types of foods that are halal and their quality and effects on an individual's mental and emotional health. This study aims to investigate the Qur'an's view of halal and good food, as well as how this understanding can affect a person's mental health in a modern context. The method used is an exploratory analysis of the Qur'anic text, with a comparative approach to contemporary scientific discoveries in psychology and mental health. The data taken came from verses of the Qur'an that explain halal food and thoyyib, as well as empirical research that links diet with mental health. The results of the study show that the Qur'an provides clear guidelines about the importance of halal and good food for the well-being of a person's soul. Consumption of foods that conform to these principles can contribute significantly to mental and emotional health, such as improving a positive psychological state and reducing the risk of mental health disorders. The conclusion of this article emphasizes the importance of considering the spiritual aspect in daily food choices to support optimal mental health. The practical implications of this study are the need for a holistic approach to mental health care, which includes understanding and practicing halal and thoyyib foods as an integral part of a spiritually and physically balanced lifestyle.